Foundations of translational ecology. Issue 10 (1st December 2017) - Enquist, Carolyn AF; Jackson, Stephen T; Garfin, Gregg M; Davis, Frank W; Gerber, Leah R; Littell, Jeremy A; Tank, Jennifer L; Terando, Adam J; Wall, Tamara U; Halpern, Benjamin; Hiers, J Kevin; Morelli, Toni Lyn; et al.
Abstract : Ecologists who specialize in translational ecology (TE) seek to link ecological knowledge to decision making by integrating ecological science with the full complement of social dimensions that underlie today's complex environmental issues. TE is motivated by a search for outcomes that directly serve the needs of natural resource managers and decision makers. This objective distinguishes it from both basic and applied ecological research and, as a practice, it deliberately extends research beyond theory or opportunistic applications. TE is uniquely positioned to address complex issues through interdisciplinary team approaches and integrated scientist–practitioner partnerships. The creativity and context‐specific knowledge of resource managers, practitioners, and decision makers inform and enrich the scientific process and help shape use‐driven, actionable science. Moreover, addressing research questions that arise from on‐the‐ground management issues – as opposed to the top‐down or expert‐oriented perspectives of traditional science – can foster the high levels of trust and commitment that are critical for long‐term, sustained engagement between partners.